Developmental and cellular functions of the ESCRT machinery in pluricellular organisms. - Michelet, X.; Djeddi, A.; Legouis, R. (Biology of the Cell, 2010)
ESCRTs (endosomal sorting complexes required for transport) were first discovered in yeast and are known to be required in the biogenesis of the MVB (multivesicular body). Most ESCRT research has been carried out in vitro using models such as yeast and mammalian cells in culture. The role of the ESCRTs genes in endosome maturation is conserved from yeast to mammals, but little is known about their function during development in multicellular organisms. Since ESCRTs play a leading role in regulating some cell signalling pathways by addressing receptors to the lysosome, it appears important to monitor ESCRT functions in multicellular models. The present review summarizes recent research on the developmental and cellular functions of the ESCRT in Caenorhabditis elegans, Drosophila melanogaster, Mus musculus or Arabidopsis thaliana.